Phase 1 Study Assessing the Pharmacokinetic Profile and Safety of Avibactam in Patients With Renal Impairment. (27th September 2016) - Merdjan, Henri; Tarral, Antoine; Das, Shampa; Li, Jianguo
Abstract: Avibactam is a non‐β‐lactam β‐lactamase inhibitor intended for use as a fixed‐dose combination with ceftazidime for the treatment of certain serious Gram‐negative infections. As avibactam is primarily excreted unchanged in the urine, renal impairment may affect its pharmacokinetics. This phase 1 study investigated the effect of renal impairment and hemodialysis on avibactam pharmacokinetics and safety. Healthy controls and subjects with increasing degrees of renal impairment received a single 30‐minute intravenous (IV) infusion of avibactam (100 mg). Anuric subjects requiring hemodialysis received the same infusion pre‐ and posthemodialysis, separated by a 7‐ to 14‐day washout. Blood and urine samples were collected, and pharmacokinetics were analyzed using noncompartmental methods. The relationships between avibactam total plasma clearance (CL) or renal clearance (CLR ) and creatinine clearance (CrCL) were evaluated by linear correlation analysis. Safety was also monitored. Increasing severity of renal impairment was associated with decreasing CL and CLR and increasing exposure and terminal half‐life (t1/2 ). Avibactam CL and CLR demonstrated an approximately linear relationship with CrCL comparable to that previously observed for ceftazidime. In patients requiring hemodialysis, >50% of the administered avibactam was removed during a 4‐hour hemodialysis session, demonstrating that avibactam should be administered after hemodialysis. No new safety findings were reported. To conclude, avibactam dose adjustment is warranted in patients with renal impairment based on the severity of impairment. Because the slope of the linear relationship between avibactam total plasma CL and CrCL is similar to that of ceftazidime, renal impairment dose adjustments should maintain the currently advised 4:1 ratio of ceftazidime:avibactam.